Hubungan antara Perceived Organizational Support dengan Job Satisfaction pada Tenaga Kependidikan Kontrak di Universitas Negeri Padang - Fajri, Mohd. Afuza Abthal; Ayu, Rindang (Al-DYAS, 2026)
This study aims to examine the relationship between Perceived Organizational Support (POS) and Job Satisfaction among contract educational staff at Universitas Negeri Padang (UNP). POS refers to employees' beliefs regarding the extent to which the organization values their contributions and cares about their well-being, while job satisfaction reflects an individual’s positive or negative attitude toward their work. A quantitative approach with a correlational design was employed. The population consisted of 488 contract staff, with a sample of 208 respondents selected through simple random sampling. Data were collected using the Perceived Organizational Support Scale developed by Eisenberger et al. (1986) and adapted by Syahputra et al. (2022), as well as the Job Satisfaction Survey (JSS) by Spector (1994), translated by Junaedi and Aisyah (2021). Data were analyzed using Spearman Rank correlation due to the non-normal distribution of the data. The results show a strong and significant positive relationship between POS and job satisfaction (ρ = 0.795; p < 0.001), indicating that higher perceived organizational support is associated with higher job satisfaction among contract staff. These findings support Organizational Support Theory and emphasize the critical role of organizational support in enhancing employees' psychological well-being and positive work attitudes. Theoretically, this study reinforces the literature on the POS–job satisfaction relationship within the higher education context, while practically offering recommendations for UNP’s management to develop human resource policies that are more supportive of contract employees.